Production of Biodegradable Sulfonated Methyl Ester by a Falling Film Reactor for ASP Flooding in EOR - Retno G. Dewi; Megawati Zunita; Permata A. Priyadi; Michael D.M. Sitompul; Annisa N. Shabrina; Faiq I. Akhiroti; Johnner Sitompul (Journal of Engineering and Technological Sciences, 2021)
Petroleum production can be improved through enhanced oil recovery (EOR) methods such as chemical injection. This study focused on sulfonation of methyl ester using SO3 dissolved in oleum compounds (H2SO4.SO3) in a mini-pilot falling film reactor at 70 °C and its application for chemical EOR with ASP flooding. The reactor was equipped with cooling water to facilitate heat transfer in view of the highly exothermic reaction. Biodegradable methyl ester sulfonate, a biosurfactant, was produced from esterification of vegetable oils, palm kernel oil, and coconut oil. The MES products were characterized by Fourier transform infrared testing, which showed S=O and -OH groups peaks, indicating that sulfonation had occurred. The IFT test data showed that the MES from CNO produced the lowest IFT values for light oil and heavy oil, equal to 11.4 mN/m and 10.3 mN/m, respectively. The effect of the MES concentration on the phase behavior was an increase of the IFT value before being applied in ASP flooding, and a decrease after reaching the optimum condition. The EOR core flooding test with the formulated ASP resulted in original oil in place (OOIP) percentages in the range of 12 to 23.5%. The highest acquisition was 23.53% OOIP for an ASP composition of 200 ppm, 0.5%wt, 2800 ppm, respectively.